Does Disclosure Regulation Work? Evidence from International IPO Markets* - Shi, Charles; Pukthuanthong, Kuntara; Walker, Thomas (Contemporary Accounting Research, 2013)
This study examines whether IPO disclosure requirements mandated by countries’ securities laws are associated with variation in IPO underpricing in international IPO markets. Our empirical analysis uses a unique sample of 6,025 IPOs from 34 countries over the period from 1995 to 2002. We show for the first time that the stringency of disclosure requirements for IPO prospectuses is negatively associated with the extent of IPO underpricing, after controlling for various country‐ and firm‐level determinants of underpricing. Moreover, we find that the disclosure effect on IPO underpricing is moderated by the extent of a country’s capital market integration. Taken together, our findings are consistent with the view that increased disclosure regulation appears to reduce IPO underpricing and hence the cost of equity, and that institutional factors such as capital market integration play an important role in understanding the economic consequences of disclosure regulation in international IPO markets.